Scalable, Robust Visualization of Very Large Trees - Beermann, Dale; Munzner, Tamara; Humphreys, Greg (EuroVis'05: Proceedings of the Joint Eurographics - IEEE VGTC Symposium on Visualization, 2005)
The TreeJuxtaposer system allowed visual comparison of large trees with guaranteed visibility of landmarks and Focus+Context navigation. While that system allowed exploration and comparison of larger datasets than previous work, it was limited to a single tree of 775,000 nodes by a large memory footprint. In this paper, we describe the theoretical limitations to TreeJuxtaposer's architecture that severely restrict its scalability. We provide two scalable, robust solutions to these limitations: TJC and TJC-Q. TJC is a system that supports browsing trees up to 15 million nodes by exploiting leading-edge graphics hardware while TJC-Q allows browsing trees up to 5 million nodes on commodity platforms. Both of these systems use a fast new algorithm for drawing and culling and benefit from a complete redesign of all data structures for more efficient memory usage and reduced preprocessing time.